Definition of the role of polyvinyl alcohol during formation and in the structure of cathodic synthesized composite electrochromic nickel hydroxide layer: template or surfactant - Kovalenko, Vadym; Kotok, Valerii; Zima, Oleksandra; Nafeev, Rovil; Verbitskiy, Volodymyr; Melnyk, Olena (Eastern-European Journal of Enterprise Technologies, 2022)
One of the promising applications of nickel hydroxide is electrochemical electrochromic devices. To significantly improve the characteristics, the role of polyvinyl alcohol (PVA) in the synthesis and structure of composite Ni(OH)2-PVA films was investigated by studying the effect of its concentration (30, 40, 50 g/l) and polymerization degree (17-99, 24-99, 30-99 types). Adhesion was investigated visually, and electrochemical and electrochromic properties – by cyclic voltammetry with simultaneous recording of optical characteristics. It was shown that at a concentration of 30 g/l, the film peeled off and had weak electrochemical and electrochromic properties. The presence of two cathodic peaks (E=500–510 mV and E=560 mV) on the cyclic voltammetry showed the presence of nickel hydroxide in the PVA matrix and nickel hydroxide with adsorbed PVA. This indicates the dual role of PVA as a surfactant and as a template. At low concentrations, the role of PVA as a surfactant prevailed. Increasing the concentration led to an increase in the film characteristics by strengthening the role of PVA as a template: at 50 g/l, the film did not peel off and has good electrochemical and electrochromic characteristics. It is shown that at a low degree of polymerization, PVA (17-99 type) mainly played the role of a surfactant but was also a template. The film cracked and had mediocre characteristics. The use of medium polymerization PVA (24-99 type) gave a film with high adhesion, electrochemical and electrochromic characteristics. It is shown that in this case, PVA performed the function of a template, there was only one cathodic peak on the voltammogram at E=500–510 mV. It was found that the use of PVA with a high degree of polymerization (30-99 type) led to a significant deterioration of the characteristics, including complete peeling of the film. This is probably due to the loss of PVA in the film